Evaluation of different wastewater treatment techniques in three WWTPs in Istanbul for the removal of selected EDCs in liquid phase - KERÇ, ASLIHAN; CAN, ZEHRA SEMRA (SPRINGER, 2014)
Endocrine-disrupting compounds (EDCs) are exogenous substances that cause adverse health effects in an intact organism, or its progeny, subsequent to the changes in endocrine function. Recent studies have shown that wastewater treatment plant effluents play an important role in the release of EDCs into aquatic environments. Therefore, in this study, influent and effluent samples from three different wastewater treatment plants (WWTPs) in Istanbul were analysed for the presence of the principal EDCs. These chemicals include steroids and synthetic organic chemicals. Thus, the occurrence and fate of EDCs of great health concern were monitored at three WWTPs in Istanbul. Furthermore, these WWTPs are employing different treatment processes. Therefore, the EDC removal performances of different treatment regimes were also evaluated. Phytosterol was the most abundant EDC in the influent samples. Second group of compounds at high influent levels were alkyl phenols. Pesticide levels of all three WWTP influent samples were low. Pasakoy Advanced WWTP is more effective at eliminating EDCs. Kadikoy Primary WWTP exhibits the lowest EDC elimination efficiencies. To the best of our knowledge, this work comprises the first detailed report on the occurrence and behaviour of both natural and synthetic EDCs in WWTPs of Istanbul and Turkey. The steroid estrogen levels of this study are higher than the previously documented values, except the levels given for Gaobeidian WWTP in Beijing, China. This is attributed to higher population densities of Beijing and Istanbul and as well as to lower individual water consumption rates in the two cities.
Keywords: Endocrine-disrupting compounds; Estrogenic steroid hormones; Wastewater treatment plant; Alkyl phenols; BPA; Phytosterol; ENDOCRINE DISRUPTING COMPOUNDS; SEWAGE-TREATMENT PLANTS; PERSONAL-CARE PRODUCTS; ESTROGENIC COMPOUNDS; ORGANIC CONTAMINANTS; AQUATIC ENVIRONMENT; STEROID ESTROGEN; TREATMENT WORKS; NONYLPHENOL; PHARMACEUTICALS